Effect of a competitive season on anthropometry and three-compartment body composition in female handball players - Milanese, C.; Piscitelli, F.; Lampis, C.; Zancanaro, C. (Biology of Sport, 2012)
The objective of this work was to investigate the anthropometry and 3-compartment body composition characteristics of female team handball players preseason and postseason. Forty-three Caucasian female handball players were recruited for this study. Linear anthropometry, skinfold measurement, and dual-energy X-ray absorptiometry (DXA) were used to investigate body dimensions and composition (fat mass, lean mass, mineral mass) over an 8-month competitive season. A complete dataset (pre- and postseason) was available for 33 handball players. Repeated measure ANOVA showed no change in body mass, BMI, sum of eight skinfolds, and most body circumferences over the season. At the total body level, bone mineral content (BMC) significantly increased postseason (+1.64%, P<0.0001), lean mass was unchanged, and fat mass and % fat mass were slightly decreased (-2.24%, P=0.295; -0.4%, P=0.229, respectively). DXA regional analysis showed that mineral mass was exclusively accrued in the upper and lower limbs postseason (upper + 4.95%, lower +1.7%, P<0.0001 for both); lean mass increased in upper (+5.3%, P<0.0001) but not lower limbs, and fat mass did not change in either. When handball players were subdivided according to competitive level (elite/sub-elite) or playing position (goalkeeper, back, pivot, wing), no significant between-group difference was found postseason in circumferences, skinfolds, and body composition parameters. In conclusion, anthropometry of female handball players does not change significantly over the competitive season except for some fat redistribution; however, BMC increases in the limbs, and lean mass in upper limbs postseason. These findings are independent of competitive level (elite/sub-elite) and playing position. These results could serve as an important tool in the development of guidelines optimizing in-season training programmes for team handball.